Greenfield on educational administration : towards a humane science - Greenfield, T. Barr; Ribbins, Peter (London : Routledge, 1993)
Greenfield on Educational Administration, a representative collection of ten of the key papers which Greenfield has written over the last twenty years, is the first volume of Greenfield's work ever to be published. These previously hard-to-find papers chart the development of his views of social reality as human invention and explore strands of argument on the nature of knowledge, on administrative theory and research, on values, on the limits of science, and on the importance of human subjectivity, truth and reality. A discussion between Greenfield and Peter Ribbins, reflecting on Greenfield's career and elaborating on the range of his complex and often controversial ideas, concludes the volume.
Chapter 1. Theory About Organization -- Chapter 2. Research in Educational Administration in the United States and Canada -- Chapter 3. Organizations as Talk, Chance, Action and Experience -- Chapter 4. Organization Theory as Ideology -- Chapter 5. The Man Who Comes Back through the Door in the Wall -- Chapter 6. Against Group Mind -- Chapter 7. The Decline and Fall of Science in Educational Administration -- Chapter 8. On Hodgkinson's Moral Art -- Chapter 9. Re-Forming and Re-Valuing Educational Administration -- Chapter 10. Science and Service -- Chapter 11. Educational Administration as a Humane Science.
Includes bibliographical references and index.
Keywords: EDUCATION MANAGEMENT